Neuroleadership Effects on Government Employee Performance: A Work Engagement Mediation Model - Pohan, Yuli Arnida; Dewi, Rosmala; Toni, Nagian (International Journal of Accounting and Economics Studies, 2026)
This study investigates how the quality of relationships between leaders and subordinates, neuroscience-informed leadership behaviors, and work ethic influence employee performance, with work engagement functioning as a mediating mechanism. Data were collected from 102 public employees in Medan, Indonesia, and analyzed using a variance-based structural equation modeling approach. The findings show that high-quality leader–subordinate relationships, neuroscience-informed leadership practices, and a strong work ethic each have a significant positive effect on employee performance. The results also reveal that leader–subordinate relationship quality and neuroscience-informed leadership enhance work engagement, whereas work ethic does not. Work engagement partially mediates the effects of leader–subordinate relationship quality and neuroscience-informed leadership on employee performance, but does not mediate the influence of work ethic. Overall, the study highlights the importance of relational leadership dynamics and neuroscience-informed leadership behaviors in strengthening work engagement and improving employee performance within the public sector.